2009
DOI: 10.1097/01.aoa.0000362057.35613.c3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Concepts in Antibiotic Prophylaxis for Cesarean Delivery: A Systematic Review

Abstract: A s the prevalence of obesity grows in the United States, rates of surgical weight-loss procedures have increased significantly, with women (particularly those of reproductive age) accounting for many of these surgeries. How this affects pregnancy is not clearly understood. The authors of this meta-analysis estimated bariatric surgery rates among women aged 18 to 45 years and reviewed the literature on the effects of these procedures on fertility rates and pregnancy outcomes.The authors searched the Nationwide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 0 publications
0
70
0
3
Order By: Relevance
“…[5][6][7][8] So, a prospective randomized clinical trial was undertaken to notice whether prophylactic antibiotic given before skin incision than after cord clamping, was more effective for preventing infectious morbidities of mother and newborn baby following caesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] So, a prospective randomized clinical trial was undertaken to notice whether prophylactic antibiotic given before skin incision than after cord clamping, was more effective for preventing infectious morbidities of mother and newborn baby following caesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…17 The timing of antibiotic prophylaxis was not specifically addressed in the review. 18 Surgical antimicrobial prophylaxis refers to a very short course of an antimicrobial agent initiated just before an operation begins. [19][20][21][22] Antimicrobial prophylaxis is an attempt to not sterilize tissues, but a critically timed adjunct used to decrease the microbial burden of intraoperative contamination to a level that cannot overwhelm host immunity.…”
Section: Introductionmentioning
confidence: 99%
“…TheUnited States has a pregnancy related deaths per 100,000 live births, with approximately 10% resulting from puerperal infection (3,4) . Caesarean section is the most important risk factor for puerperal infection (5) . In the present study it is found that postoperative complications are more in emergency Caesarean group (58%) as against 23% in elective group.…”
Section: Discussionmentioning
confidence: 99%
“…ACOG recommends the use of a single dose of a narrow spectrum first generation cephalosporin or a single dose of clindamycin with an amino glycoside for those with penicillin allergy, as prophylaxis for Caesarean delivery. (5,10) .Urinary tract infection can be brought down by the policy of avoiding catheterisation as far as possible in primary Caesarean sections. The mean day of suture removal between the two groups did not have any significant difference.…”
Section: Discussionmentioning
confidence: 99%